Who Will Be a Bystander? An Exploratory Study of First-Person Perception Effects on Campus Bystander Behavioral Intentions - Mercer Kollar, Laura M.; Peng, Lulu; Ports, Katie A.; Shen, Lijiang (Journal of family violence, 2020)
The purpose was to explore the underlying mechanisms that drive relationships between knowledge, attitudes and intervening bystander behavior to improve bystander violence prevention program effectiveness. Perceptual effects theory was used to understand third-person and first-person perceptions (TPP and FPP) as related to bystander intervention programs and to what extent perceptual gaps influence one’s intention to intervene. A web-based survey was conducted with 379 undergraduate students recruited from a large, Northeastern University. The survey covered demographics, previous bystander training, self-efficacy to engage in bystander behavior, social desirability of bystander intervention training programs, and perceived effects on self and others. Participants indicated how they would act in six hypothetical dating violence/bullying and sexual violence scenarios, and how they thought an average student on campus would act. Perceived ambiguity and risk for each of the scenarios were also measured. Descriptive statistics, paired-sample t-tests, and multilevel model analyses were conducted. Results showed that a robust first-person perception effect existed (i.e., the student perceived themselves being more influenced by bystander interventions/messages than their peers). The magnitude of FPP was increased by sex (significantly larger gap among female students) and previous training. Results show promise to further tailor and refine bystander interventions and provide directions to improve program effectiveness. Despite study limitations, the results indicate the first-person effect warrants further consideration for programming and messaging. Tailoring bystander training or repeated exposure may increase bystander behaviors. More research is needed to fully uncover TPP/FPP effects, predictors, and impacts on bystander intervention programs.